1981
DOI: 10.1146/annurev.ne.04.030181.001421
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in the Vestibulo-Ocular Reflex: A New Hypothesis

Abstract: The vestibulo-ocular reflex functions to prevent head movements from disturbing retinal images by generating compensatory eye movements to offset the head movements. In the monkey--the species mainly under consideration here--this reflex is machine-like and very effective. In the short-term, the VOR operates as an open-loop control system without the benefit of feedback and its performance is fixed and immutable: No matter what pattern of eye-head coordination the animal uses to view external objects, there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
258
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 598 publications
(270 citation statements)
references
References 0 publications
12
258
0
Order By: Relevance
“…The reversibility of plasticity at gr3Pk j synapses is at present an assumption of the simulation because the evidence to date suggests that LTP-LTD at this synapse are not mutually reversible because the expression of the former seems to be presynaptic (Salin et al, 1996), whereas that of the later is clearly postsynaptic (Linden, 1994). As first suggested by Miles and Lisberger (1981) and supported more recently by theoretical (Medina and and empirical (Perrett and Mauk, 1995;Aizenman and Linden, 2000) analyses, plasticity in the cerebellar nucleus was controlled by Purkinje cell inputs. Thus, the excitatory mf3nuc synapses underwent LTD when active during strong inhibitory input from the Purkinje cells and LTP when active during a transient pause in this inhibition.…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…The reversibility of plasticity at gr3Pk j synapses is at present an assumption of the simulation because the evidence to date suggests that LTP-LTD at this synapse are not mutually reversible because the expression of the former seems to be presynaptic (Salin et al, 1996), whereas that of the later is clearly postsynaptic (Linden, 1994). As first suggested by Miles and Lisberger (1981) and supported more recently by theoretical (Medina and and empirical (Perrett and Mauk, 1995;Aizenman and Linden, 2000) analyses, plasticity in the cerebellar nucleus was controlled by Purkinje cell inputs. Thus, the excitatory mf3nuc synapses underwent LTD when active during strong inhibitory input from the Purkinje cells and LTP when active during a transient pause in this inhibition.…”
Section: Methodsmentioning
confidence: 81%
“…Based on empirical evidence, plasticity in the cerebellar cortex was controlled by climbing fiber inputs such that gr3Pkj synapses active during a climbing fiber input decreased in strength (LTD) and those active in the absence of a climbing fiber input increased in strength (LTP) (Sakurai, 1987;Ito, 1989;Hirano, 1990;Shibuki and Okada, 1992;Linden, 1994;Salin et al, 1996). As first suggested by Miles and Lisberger (1981) and supported more recently by theoretical and empirical (Perrett and Mauk, 1995;Aizenman and Linden, 2000) analyses, plasticity in the cerebellar nucleus was controlled by inhibitory inputs from Purkinje cells. Thus, LTD of mf3nuc synapses occurred during strong inhibitory Purkinje cell inputs, whereas LTP was induced during transient pauses in this inhibition.…”
Section: Simulations Show Savings Attributable To Residual Plasticitymentioning
confidence: 93%
“…The existence of an analogous form of plasticity in the vestibular nucleus and the notion that its induction is controlled by inputs from Purkinje cells was first suggested by Miles and Lisberger (1981) for another form of cerebellar motor learning known as vestibulo-ocular reflex (VOR) adaptation, and evidence in support of this view has been obtained in subsequent studies (Lisberger, 1994;du Lac et al, 1995). The present findings underscore the similarities between eyelid conditioning and adaptation of the VOR, in that they are both forms of cerebellar motor learning that induce plasticity at two sites, one in the cerebellar cortex and another in their target neurons in the deep cerebellar/vestibular nuclei.…”
Section: Cerebellar Learning Induces Plasticity In Target Nuclei Downmentioning
confidence: 99%
“…In principle, the plasticity could be driven by the activity in any of the inputs to the AIN or by activity in the AIN itself (Medina and Mauk, 1999). Miles and Lisberger (1981) first proposed that Purkinje cells could control the induction of synaptic changes in the deep cerebellar/vestibular nuclei, and subsequent computational studies were in agreement (Medina and Mauk, 1999). Recent studies have shown that rebound excitation of AIN neurons following burst-pause modulation of Purkinje cell activity is sufficient to increase both the intrinsic excitability of AIN neurons (Zhang et al, 2004) and the strength of mossy fiber synapses (Pugh and Raman, 2006).…”
Section: Candidate Plasticity Mechanisms Underlying Slrsmentioning
confidence: 99%
See 1 more Smart Citation